Cooperative design, visualization, and engineering : 14th International Conference, CDVE 2017, Mallorca, Spain, September 17-20, 2017, Proceedings /: 14th International Conference, CDVE 2017, Mallorca, Spain, September 17-20, 2017, Proceedings. (2017) - Unknown
No abstract available